Design Thinking: Employing an Effective Multidisciplinary Pedagogical Framework to Foster Creativity and Innovation in Rural and Remote Education - Anderson, Neil (Australian and International Journal of Rural Education, 2012)
This paper outlines a project to develop and track 'design thinking' skills within groups of students in late primary and early secondary years of schooling in order to strengthen their creative skills and innovative mindsets. The outcome of the research will be the development of a model for the broad-based implementation of design thinking in schools which will foster students' creative skills, critical for 21st century living and their capacity to make a strong contribution to innovation in their future workplaces. Students will develop competence in using the steps - 'understand, observe, visualise, evaluate, refine and implement' - in relation to examining contemporary issues concerned with living in rural and remote areas and will subsequently design illustrative multimedia presentations or computer games. Design thinking as a framework to solve problems and/or as a pedagogical framework has emerged from the processes that designers have used over the last twenty years to create unique and innovative products. A convincing literature base has continued to grow across almost every discipline area, yet 'design thinking' is only just starting to influence school-based education.